2006
DOI: 10.1530/eje.1.02080
|View full text |Cite
|
Sign up to set email alerts
|

Fetal microchimerism in Hashimoto’s thyroiditis: a quantitative approach

Abstract: Objective: Fetal microchimerism (MCH) has been implicated in the etiology of autoimmune diseases such as autoimmune thyroiditis. The goal of the study was to reliably estimate the number of fetal engrafted cells and to further investigate factors influencing the development of MCH. Methods: Quantitative real-time PCR amplification using Y-chromosome specific (DYS14) and autosomal (b-globin) loci was performed on thyroid gland specimens. Furthermore, we compared the distribution of ABO and rhesus systems in mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 32 publications
1
51
0
5
Order By: Relevance
“…(Davies 1999), (Ando et al 2002;Klintschar et al 2001) Recently, using a quantitative PCR assay, fetal Mc was detected in 8 of 21 thyroid samples from women with Hashimoto's disease compared to 0 of 17 healthy thyroid glands. (Ando et al 2002;Klintschar et al 2001;Klintschar et al 2006) In thyroidectomy and autopsy specimens from women with multiple thyroid disorders, male cells were found using fluorescence in situ hybridization (FISH) in thyroids from more than half of women with a thyroid disease compared to none in autopsy controls. (Klintschar et al 2006) A large community-based study showed no association between parity and presence of thyroid antibodies or thyroid dysfunction and suggested a lesser role for fetal Mc in autoimmune thyroid disease.…”
Section: A Fetal Microchimerism In Systemic Sclerosis and Autoimmunementioning
confidence: 99%
See 1 more Smart Citation
“…(Davies 1999), (Ando et al 2002;Klintschar et al 2001) Recently, using a quantitative PCR assay, fetal Mc was detected in 8 of 21 thyroid samples from women with Hashimoto's disease compared to 0 of 17 healthy thyroid glands. (Ando et al 2002;Klintschar et al 2001;Klintschar et al 2006) In thyroidectomy and autopsy specimens from women with multiple thyroid disorders, male cells were found using fluorescence in situ hybridization (FISH) in thyroids from more than half of women with a thyroid disease compared to none in autopsy controls. (Klintschar et al 2006) A large community-based study showed no association between parity and presence of thyroid antibodies or thyroid dysfunction and suggested a lesser role for fetal Mc in autoimmune thyroid disease.…”
Section: A Fetal Microchimerism In Systemic Sclerosis and Autoimmunementioning
confidence: 99%
“…(Ando et al 2002;Klintschar et al 2001;Klintschar et al 2006) In thyroidectomy and autopsy specimens from women with multiple thyroid disorders, male cells were found using fluorescence in situ hybridization (FISH) in thyroids from more than half of women with a thyroid disease compared to none in autopsy controls. (Klintschar et al 2006) A large community-based study showed no association between parity and presence of thyroid antibodies or thyroid dysfunction and suggested a lesser role for fetal Mc in autoimmune thyroid disease. (Walsh et al 2005) However, the number of pregnancies may be a less important risk factor than HLA relationships between fetal and maternal cells, as suggested by studies in systemic sclerosis.…”
Section: A Fetal Microchimerism In Systemic Sclerosis and Autoimmunementioning
confidence: 99%
“…By this and other methods, FCM has been extensively studied in autoimmune diseases, particularly systemic ones, because they are more often observed in females and appear to be modulated by pregnancy (5,6,7,8). As far as autoimmune thyroid disease (AITD) is concerned, FCM has been documented in Hashimoto's thyroiditis (HT) and Graves' disease (GD) (9,10,11,12,13). These diseases occur more frequently in women, with a peak incidence during the fertile age.…”
Section: Introductionmentioning
confidence: 99%
“…They appear to be related to pregnancy and often have a spontaneous resolution after delivery and an onset or exacerbation in the postpartum period, although their relation with parity is still controversial (14,15,16). In the few available series, which include a limited number of cases, FCM was found to be represented more at the tissue level in HT and GD as compared to non-AITDs (4,9,10,11,12,13,17). Even at the peripheral level, scanty and discrepant results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Male microchimeric cells have been demonstrated in higher frequency in normal and benign breast tissues than in malignant breast lesions [19]. Similarly, lower frequency of chimerism detected in peripheral blood was identified in women with papillary thyroid cancer and hematological malignancies, including non-Hodgkin lymphoma (nHL) [6,[20][21][22][23]. Evidence of lower frequency or degree of chimerism has been interpreted as a protective effect of the chimeric cells against these cancers in women.…”
Section: Introductionmentioning
confidence: 99%